Targeting peptide‐based quorum sensing systems for the treatment of gram‐positive bacterial infections. Issue 2 (12th November 2022) - Milly, Tahmina A.; Tal‐Gan, Yftah
Abstract: Bacteria utilize a cell density‐dependent communication system called quorum sensing (QS) to coordinate group behaviors. In Gram‐positive bacteria, QS involves the production of and response to auto‐inducing peptide (AIP) signaling molecules to modulate group phenotypes, including pathogenicity. As such, this bacterial communication system has been identified as a potential therapeutic target against bacterial infections. More specifically, developing synthetic modulators derived from the native peptide signal paves a new way to selectively block the pathogenic behaviors associated with this signaling system. Moreover, rational design and development of potent synthetic peptide modulators allows in depth understanding of the molecular mechanisms that drive QS circuits in diverse bacterial species. Overall, studies aimed at understanding the role of QS in microbial social behavior could result in the accumulation of significant knowledge of microbial interactions, and consequently lead to the development of alternative therapeutic agents to treat bacterial infectivity. In this review, we discuss recent advances in the development of peptide‐based modulators to target QS systems in Gram‐positive pathogens, with a focus on evaluating the therapeutic potential associated with these bacterial signaling pathways. Abstract :